Primary Non-Hodgkin lymphoma of the tongue with cervical lymph node involvement: A rare presentation masquerading squamous cell carcinoma - Bhatia, Akanksha; Gupta, Prajwala; Jain, Swasti; Chauhan, Devender Singh; Bhardwaj, Minakshi (Indian Journal of Case Reports, 2020)
Primary non-Hodgkin lymphoma (NHL) of the tongue is extremely rare. We present here a case of primary diffuse large B cell NHL, non-germinal center type in a 60-year-old female, who presented with a mass in the base of the tongue and vallecula with cervical lymphadenopathy. Clinically, a diagnosis of squamous cell carcinoma was kept. Fine-needle aspiration cytology was useful in the early diagnosis of the intraoral NHL involving a cervical lymph node.